YASHIL GOL’S ECO-TOURISM POTENTIAL: STUDY CASE - Mammadova, Ulviyya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The richest eco-tourism potential and real ecosystem of Yashil Gol were studied using remote sensing methods in aerospace sources. Based on these materials, the eco-geographical factors of the lake were revealed using OpenStreetMap and Google Earth. The lake territory comprises 2,551 m² (0.26 ha), and the total perimeter of the lake circle is 202.4 m. The lake’s absolute height is about 909 m above sea level, and the relative height is 1.37 km. The lake shape resembles an oval leaf from space. Consequently, the map length is 76.60 m, but the ground length is approximately 76.96 m, with a heading of 193.43° on the Google Earth map. The lake’s map width is 63.37 m, but the ground width reaches 63.39 m, with a heading of 90.59 ° on the Google Earth map. Yashil Gol is located at 40°45'35